The Long-Term Urological Consequences of Anabolic Steroid Abuse: A Narrative Review: Konsekuensi Urologi Jangka Panjang dari Penyalahgunaan Steroid Anabolik: Sebuah Narasi - Reza, Muhammad Alfi; Krisna, Muhammad Sidharta; Diennillah, Fathannia Rizky; S. , Suriani; Yulianto, Andy (Journal of Aafiyah Health Research (JAHR), 2024)
ABSTRACT Background: Anabolic-Androgenic Steroids (AAS) have been widely used to enhance muscle mass and physical performance. However, their prolonged use has been associated with various adverse effects on urological health, including hypogonadism, infertility, erectile dysfunction (ED), and benign prostatic hyperplasia (BPH). Suppression of the hypothalamic-pituitary-gonadal (HPG) axis due to AAS leads to significant hormonal imbalances and long-term reproductive consequences. Objective: This study aims to review the urological effects of AAS, focusing on their impact on testosterone levels, spermatogenesis, erectile function, and prostate health. The review highlights potential risks and clinical implications for individuals using AAS. Method: A narrative review was conducted by analyzing relevant studies from PubMed, Scopus, and Science Direct published between 2014-2024. Articles were selected based on their relevance to the impact of AAS on urological health, particularly hypogonadism, infertility, ED, and BPH. Data from clinical trials, cohort studies, and systematic reviews were synthesized to provide a comprehensive analysis. Results: Chronic AAS use significantly reduces endogenous testosterone production, leading to hypogonadism and associated symptoms such as fatigue, decreased libido, and mood disturbances. Studies indicate a strong correlation between AAS use and impaired spermatogenesis, with some cases resulting in irreversible infertility. Moreover, AAS users have a higher prevalence of ED compared to non-users due to hormonal imbalances and psychological factors. Excessive androgen stimulation is also linked to an increased risk of prostate enlargement, potentially leading to urinary complications. Conclusion: The long-term use of AAS poses substantial risks to urological health, necessitating awareness and early intervention. Regular medical monitoring and cessation strategies are essential to mitigate these adverse effects. Further research is needed to develop effective rehabilitation and treatment options for individuals experiencing AAS-related urological complications.